Blood-brain barrier, cytotoxic chemotherapies and glioblastoma. (1st November 2016) - Dréan, Antonin; Goldwirt, Lauriane; Verreault, Maïté; Canney, Michael; Schmitt, Charlotte; Guehennec, Jeremy; Delattre, Jean-Yves; Carpentier, Alexandre; Idbaih, Ahmed
ABSTRACT: Introduction : Glioblastomas (GBM) are the most common and aggressive primary malignant brain tumors in adults. The blood brain barrier (BBB) is a major limitation reducing efficacy of anti-cancer drugs in the treatment of GBM patients. Areas covered : Virtually all GBM recur after the first-line treatment, at least partly, due to invasive tumor cells protected from chemotherapeutic agents by the intact BBB in the brain adjacent to tumor. The passage through the BBB, taken by antitumor drugs, is poorly and heterogeneously documented in the literature. In this review, we have focused our attention on: (i) the BBB, (ii) the passage of chemotherapeutic agents across the BBB and (iii) the strategies investigated to overcome this barrier. Expert commentary : A better preclinical knowledge of the crossing of the BBB by antitumor drugs will allow optimizing their clinical development, alone or combined with BBB bypassing strategies, towards an increased success rate of clinical trials.